울릉도에서의 화산과정과 발생 가능한 분출유형의 평가 - 황상구(Sang Koo Hwang); 정성욱(Seong Wook Jeong); 류한영(Han Young Ryu); 손영우(Young Woo Son); 권태호(Tae Ho Kwon) (자원환경지질, 2020)
Volcanostratigraphy in Ulleung Island is divided into 4 stratigraphic groups: Dodong Basaltic Rocks, Ulleung Group, Seonginbong Group and NariGroup. The main pyroclastics in them includes lapilli tuff intercalated within the Dodong Basaltic Rocks, lapilli tuff at the top of Sadong Breccia, Sataegam Tuff, Gombawi Welded Tuff, Bongrae Scoria Deposits, Maljandeung Tuff, Nari Scoria Deposits and Jugam Scoria Deposits. Analysing eruption types, The lapilli tuff in the Dodong Basaltic Rocks is derived from Surtseyan eruption, and the Bongrae, Nari and Jugam Scoria Deposits are caused by Strombolian eruptions or/and sub-Plinion eruptions, but the Sataegam Tuff and Maljandeung Tuff are derived from Plinian and phreatoplinian eruptions. Among them the large-scaled eruptions. In particular, the eruptions of Maljandeung were large enough to result in caldera collapse, and had falled out tephras to the eastern Korean peninsula but even Japan Islands. The magma with high potential to be still alive is judged to be trachyandesitic and phonolitic in composition. If the trachyandesitic magma explodes, it will probably result in a strombolian eruption and have a fairly low explosivity, but if the phonolitic magma explodes, it will probably result in a plinian eruption and have a much higher explosivity. If the eruption had a high explosivity, there is a possibility that it could easily be converted into a phreatoplinian eruption due to the influx of groundwater by the easy generation of fractures. These large-scaled eruptions could fall out tephras to the eastern Korean peninsula but even Japan Islands. 울릉도에서 화산층서는 도동현무암질암류, 울릉층군, 성인봉층군과 나리층군 등의 4개 층군으로 구분된다. 그 중에 화성쇄설암층은 도동현무암질암류에 협재하는 라필리응회암, 사동각력암 상부의 라필리응회암, 사태감응회암, 곰바위 용결응회암, 봉래분석층, 말잔등응회암, 나리분석층과 죽암분석층 등이 있다. 분출유형을 살펴보면 도동현무암질암류 내의 라필리응회암은 써쩨이언 분출에 의한 것이고 봉래분석층, 나리분석층과 죽암분석층은 소규모 스트롬볼리언 분출 혹은/및 저플리니언 분출에 의한 것이지만, 사태감응회암과 말잔등응회암은 대규모 플리니언 분출과 수증기플리니언 분출에 의한 것이다. 특히 말잔등응회암의 분출은 칼데라를 형성할 만큼 규모가 컸었으며, 한반도 동해안과 일본 열도까지도 영향을 미쳤을 것으로 분석된다. 아직도 살아있을 잠재성 높은 마그마는 조면안산암질과 포놀라이트질로 판단된다. 조면안산암질 마그마가 폭발한다면 아마도 스트롬볼리언 분출로 발생하여 폭발강도가 상당히 낮겠지만, 포놀라이트질 마그마가 터진다면 플리니언 분출로 폭발강도는 훨씬 더 커질 것이다. 그 분출이 높은 폭발강도를 가진다면, 단열의 발생빈도도 커질 것이고 그에 따라서 지하수의 유입으로 인해 수증기플리니언 분출로 쉽게 전환될 가능성도 있을 것이다. 이러한 대규모 분출은 한반도 동해안과 일본열도까지도 테프라를 확산시킬 수 있다.